Structural features of the reprolysin atrolysin C and tissue inhibitors of metalloproteinases (TIMPs) interaction. - Pinto, A; Terra, R; Guimarães, J; Kashiwagi, M; Nagase, H; Serrano, S; Fox, J (2006)
Atrolysin C is a P-I snake venom metalloproteinase (SVMP) from Crotalus atrox venom, which efficiently degrades capillary basement membranes, extracellular matrix, and cell surface proteins to produce hemorrhage. The tissue inhibitors of metalloproteinases (TIMPs) are effective inhibitors of matrix metalloproteinases which share some structural similarity with the SVMPs. In this work, we evaluated the inhibitory profile of TIMP-1, TIMP-2, and the N-terminal domain of TIMP-3 (N-TIMP-3) on the proteolytic activity of atrolysin C and analyzed the structural requirements and molecular basis of inhibitor-enzyme interaction using molecular modeling. While TIMP-1 and TIMP-2 had no inhibitory activity upon atrolysin C, the N-terminal domain of TIMP-3 (N-TIMP-3) was a potent inhibitor with a K(i) value of approximately 150nM. The predicted docking structures of atrolysin C and TIMPs were submitted to molecular dynamics simulations and the complex atrolysin C/N-TIMP-3 was the only one that maintained the inhibitory conformation. This study is the first to shed light on the structural determinants required for the interaction between a SVMP and a TIMP, and suggests a structural basis for TIMP-3 inhibitory action and related proteins such as the ADAMs.